Pulmonale granulomatöse Erkrankungen und pulmonale Manifestationen systemischer Granulomatosen = Pulmonary granulomatous diseases and pulmonary manifestations of systemic granulomatous disease - Piel, Stella; Kreuter, Michael; Herth, Felix; Kauczor, Hans-Ulrich; Heußel, Claus Peter (Der Radiologe, 2016)
Clinical/methodical issueGranulomas as signs of specific inflammation of the lungs are found in various diseases with pulmonary manifestations and represent an important imaging finding.Standard radiological methodsThe standard imaging modality for the work-up of granulomatous diseases of the lungs is most often thin-slice computed tomography (CT). There are a few instances, e. g. tuberculosis, sarcoidosis and silicosis, where a chest radiograph still plays an important role.Methodical innovationsFurther radiological modalities are usually not needed in the routine work-up of granulomatous diseases of the chest. In special cases magnetic resonance imaging (MRI) and positron emission tomography (PET)-CT scans play an important role, e. g. detecting cardiac sarcoidosis by cardiac MRI or choline C‑11 PET-CT in diagnosing lung carcinoma in scar tissue after tuberculosis.PerformanceThe accuracy of thin-slice CT is very high for granulomatous diseases.AchievementsIn cases of chronic disease and fibrotic interstitial lung disease it is important to perform thin-slice CT in order to diagnose a specific disease pattern. Thin-slice CT is also highly sensitive in detecting disease complications and comorbidities, such as malignancies. Given these indications thin-slice CT is generally accepted in the routine daily practice.Practical recommendationsA thin-slice CT and an interdisciplinary discussion are recommended in many cases with a suspected diagnosis of pulmonary granulomatous disease due to clinical or radiographic findings.